NIAT PERILAKU MENGGUNAKAN APLIKASI KESEHATAN GRAB HEALTH SELAMA MASA PANDEMIK COVID-19 - Maria Lusia Viany Noel; Didik Setyawan; Nang Among Budiadi (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This research aims to examine the effect of behavioural intention using the Grab Health application during the Covid19 pandemic. Data was obtained from questionnaires were distributed to the general public who use health applications Grab Health. The sampling technique used is non probability sampling, that is convenience sampling technique. The sample used in the study was 200 respondents who used the health applications Grab Health. Hypothesis testing is done by the Structural Equation Modeling (SEM) analysis method using the AMOS program. The results of this research indicate that attitudes have a significant effect on behavioral intentions, positive perceptions of perceived enjoyment are significant to attitudes, social influences have a significant influence on attitudes, and perceptions of vulnerability do not significantly influence attitudes in the use of health applications Grab Health